Structural and Physical Properties of the Vacancy Doped Systems, R₍₁₋ᵪ₎TiO₃ (R=Nd for 0.00≤x≤.33 and Sm for 0.00≤x≤0.17): An Investigation of Metal-Insulator Transitions - Amow, Gisele (My University, 1999)
Members of the solid solutions, R₍₁₋ᵪ₎TiO₃ (R=Nd, Sm) have been prepared for 0.00≤x≤0.33 and 0.00≤x≤0.17 for R=Nd and Sm respectively. Three structural types have been identified for the R=Nd system: Pnma (0.00≤x≤0.17), Pban (0.25≤x≤0.30) and P4/mmm (x=0.33). For the R=Sm system, only the Pnma structure type has been identified by x-ray powder diffraction. D.c. susceptibility measurements reveal canted antiferromagnetic behaviour for the nominal x= 0.00 and 0.05 compositions in both systems. The observed Neel temperatures are 100K and 75K respectively for x=0.00 and 0.05 in the Nd₍₁₋ᵪ₎TiO₃ system and 50K and 42K for the x= 0.00 and 0.05 compositions in the Sm₍₁₋ᵪ₎TiO₃ system. The magnetic structures of these phases have been determined using neutron diffraction methods. Paramagnetic behaviour is observed for x≥0.10 in both systems. Four probe van der Pauw measurements reveal two metal-insulator transitions in the Nd₍₁₋ᵪ₎TiO₃ system at x= 0.10 and x=0.25 and only one for the Sm₍₁₋ᵪ₎TiO₃ system at x=0.10. In the metallic regime, the resistivity behaviour indicates these compounds are poor metals with highly correlated behaviour possibly associated with the Kondo effect and Fermi liquid character. Further investigation of these "metallic" phases by specific heat measurements reveal a divergence of the carrier mass as the Mott transition is approached from the itinerant side in accordance with the Brinkmann-Rice model. Thermopower measurements in both systems reveal the presence of p-type conduction in the Mott insulator phases, while n-type conduction is observed for x ≥ 0.10. The thermopower behaviour of the "metallic" phases can be described using Mott's law for metals.
Keywords: Chemistry; Chemistry